Pengaruh Persentase Jumlah Pakan Buatan Yang Berbeda Terhadap Pertumbuhan dan Kelulushidupan Keong Macan (Babylonia spirata L.) - Fransiska, Fransiska; Rachmawati, Diana; Samidjan, Istiyanto (Journal of Aquaculture Management and Technology, 2013)
Spettedbabylon(Babylonia spirata L.) is a member of gastropod species are important economic value, so the potential for propagation. Cultivation begins with the discovery of artificial feed derived from fish meal and flour of green mussels as a source of animal protein to feed artificial leopard slugs. Green mussel (Perna viridis) is known as a cheap source of animal protein and rich in essential amino acids (arginine, leucine, lysine). In addition, mussels flour can be substituted in place of fish meal that can be used as an artificial feed. This study aimed to determine the effect of feeding with a different percentage of the amount of feed and figure out the percentage of feed that gives the best effect for growth, and survival spettedbabylon. The material used is a spettedbabylon(Babylonia spirata L.) with an average weight of 15.81 ± 0.02 g / fish originating from Jepara waters. Spettedreared in a plastic container with a basket volume 4 liters of water with 2 stocking density tail / liter, so that each unit there are 8 tails maintenance / container. Test feed is feed-shaped pasta made with flour protein content of 35% green mussels as a source of animal protein. The method used is performed using experimental laboratory methods. Completely Randomized Design (CRD) that is 3 treatments and 3 replications. A treatment (percentage of feed 3%), B (percentage of feed 5%), C (percentage of feed 7%). Data were analyzed using analysis of variance followed by Duncan's test. This study was conducted in November 2011 s / d in February 2012 in BBPBAP Jepara, Central Java. The results showed that the percentage of different artificial feed on snails tiger (Babylonian spirata L.) significantly (P <0.05) on the specific growth rate (SGR), Protein Efficiency Ratio (PER), was highly significant(P <0.01) on the efficiencyof feed utilization(EPP), but no significant effect on survival (SR) leopard slug. Treatment A (3%) give the best effect on SGR (0.09 ± 0.02), SR (95.83 ± 7.22) PER (32.84 ± 06,40), EPP (2.50 ± 0, 40) and SR (7.22 ± 95.83). Water quality is still within the normal range for tiger snail farming activities with the 26.9-30o temperature, salinity 31-32 ppt, pH 7-8, DO from 3.9 to 4 mg / liter undetectable ammonia, nitrate and nitrite 0.005 0.011.